(untitled) (Clinics, 2008)
OBJECTIVES: To compare conventional and transdisciplinary care in a tertiary outpatient clinic for patients after their first acute myocardial infarction. METHODS: One hundred fifty-three patients with acute myocardial infarction were randomized at hospital discharge and followed-up to compare conventional (n=75) and transdisciplinary care (n=78). They were submitted to a clinical evaluation, received a dietary plan, and were re-evaluated twice in 60-180 days by a nurse, dietitian and physician, when new clinical and laboratory data were collected. The primary outcome was clinical improvement, as evaluated by an index including reduction of body weight, lowering of blood pressure, smoking cessation, increase in physical activity and compliance with medication. RESULTS: The groups were similar at baseline: 63.4% were men, 89.9% had an acute myocardial infarction with ST-segment-elevation, 32.7% were diabetic, and 72.2% were hypertensive. The clinical improvement index was similar between the studied groups: in 33.3 % (transdisciplinary care) vs. 30.4 % (conventional care) of patients, the improvement was very good (P=1.000). Rates of re-hospitalization and death (p=0.127) were similar between transdisciplinary and conventional care. Compliance with diet was higher for transdisciplinary care (50.0%) vs. conventional care (26.1%) (p=0.007), as was compliance with visits (73.3 vs. 40.3%, respectively, p